The Usage of Momordica charantia as Face Cleansing Cosmetics: Momordica charantia Leaves Extract as Absorbent of Heavy Metal, Surface Tension Reducer and Skin Antibacterial - Dimas Andrianto; Popi Asri Kurniatin; Silvy Aulya; Dewi Eriyanti (IPB University, 2016)
Momordica charantia (daun pare in Indonesian) is one of Indonesian herbal plants which useful property has not been explored. M. charantia contains chemical substances such as oil and saponin. Nowadays, the society possesses a high awareness regarding the risk of using artificial chemicals for skin care and more people are switching to use herbal cosmetics. The extract of M. charantiahas been proven to be able to be used as one of the active components of herbal based facial cleansing cosmetics. Its active properties include its ability to absorb heavy metal from air pollution and motor vehicles emission, decrease surface tension, and to act as an antibacterial agent.In the research, M.charantia was extracted using 4 (four) solvents, namely water, ethanol, methanol, and hexane. The research then examined the property of each extract in metal absorption (using Atomic Absorption Spectrophotometry / AAS), decreasing surface tension, and antibacterial activities. The result of the test showed that the water based extract was the most effective extract in reducing surface tension and in inhibiting the development of Escherichia coli and Staphylococcus aureus bacteria, while the ethanol based extract was the most effective one in absorption of Pb and Hg metals and in inhibiting the development of Staphylococcus epidermidis bacteria. The result indicated that M. charantiaextract has the potentials to be used as facial cleanser and can also counter the bacterial infection which could cause acnes.